Fluorescent Indicators For Biological Imaging of Monatomic Ions - Wu, Sheng-Yi; Shen, Yi; Shkolnikov, Irene; Campbell, Robert E. (Frontiers in Cell and Developmental Biology, 2022)
Monatomic ions play critical biological roles including maintaining the cellular osmotic pressure, transmitting signals, and catalyzing redox reactions as cofactors in enzymes. The ability to visualize monatomic ion concentration, and dynamic changes in the concentration, is essential to understanding their many biological functions. A growing number of genetically encodable and synthetic indicators enable the visualization and detection of monatomic ions in biological systems. With this review, we aim to provide a survey of the current landscape of reported indicators. We hope this review will be a useful guide to researchers who are interested in using indicators for biological applications and to tool developers seeking opportunities to create new and improved indicators.